Scalable Thousand Channel Penetrating Microneedle Arrays on Flex for Multimodal and Large Area Coverage BrainMachine Interfaces. (25th February 2022) - Lee, Sang Heon; Thunemann, Martin; Lee, Keundong; Cleary, Daniel R.; Tonsfeldt, Karen J.; Oh, Hongseok; Azzazy, Farid; Tchoe, Youngbin; Bourhis, Andrew M.; Hossain, Lorraine; Ro, Yun Goo; Tanaka, Atsunori; et al.
Abstract: The Utah array powers cutting‐edge projects for restoration of neurological function, such as BrainGate, but the underlying electrode technology has itself advanced little in the last three decades. Here, advanced dual‐side lithographic microfabrication processes is exploited to demonstrate a 1024‐channel penetrating silicon microneedle array (SiMNA) that is scalable in its recording capabilities and cortical coverage and is suitable for clinical translation. The SiMNA is the first penetrating microneedle array with a flexible backing that affords compliancy to brain movements. In addition, the SiMNA is optically transparent permitting simultaneous optical and electrophysiological interrogation of neuronal activity. The SiMNA is used to demonstrate reliable recordings of spontaneous and evoked field potentials and of single unit activity in chronically implanted mice for up to 196 days in response to optogenetic and to whisker air‐puff stimuli. Significantly, the 1024‐channel SiMNA establishes detailed spatiotemporal mapping of broadband brain activity in rats. This novel scalable and biocompatible SiMNA with its multimodal capability and sensitivity to broadband brain activity will accelerate the progress in fundamental neurophysiological investigations and establishes a new milestone for penetrating and large area coverage microelectrode arrays for brain–machine interfaces. Abstract : Arrays of microneedles on flexible substrates can be more compliant to brain movements and pave the way for high‐fidelity brain–machine interfaces. Here, a novel and scalable fabrication procedure is used to demonstrate such microneedles and assess them in anesthetized and chronically implanted small animals.